PENYELESAIAN KONFLIK KEAGAMAAN DI INDONESIA (SEBUAH REFLEKSI DARI PENGALAMAN SEJARAH HINDU) - I Ketut Widnya (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2018)
There are five main sects that have ever grown and developed in the history of Hinduism.The 5 sects are: Sivaism, Vaisnava, Sakta, Sora, and Ganapatya. The teachings of all sects comefrom the Vedic scriptures. But each sect selects certain aspects of the Vedic teachings and givesinterpretations in accordance with the prevailing traditions in each sect. As a result, there arevariants of teachings that differ from one sect to another. Conflict can be a process that isinstrumental in the formation, integration and maintenance of social structures. Conflict canestablish and maintain a boundary line between two or more groups. Conflict with other groupscan reinforce group identity and protect it so that it does not melt into the social world around it.Outgroupsconflict can strengthen the identity of group members so that conflict carries out apositive function in strengthening ingroupidentity (Poloma, 2003: 107108).The dynamics ofsyncretism between various sects and subsectswithin Hinduism, which are expressed in thelong chain of Indonesian cultural history, are not only unique religious symptoms, the greatestand still alive today, but also a right choice to overcome fluralism of the nation's problems.Keywords: Settlement, Religious Conflict, Indonesia, Hindu History Experience